Comparison of resident and mid-level provider productivity and patient satisfaction in an emergency department fast track. Issue 1 (12th March 2012) - Jeanmonod, Rebecca; DelCollo, Jessica; Jeanmonod, Donald; Dombchewsky, Orest; Reiter, Mark
Abstract : Objective: To evaluate productivity of mid-level providers (MLPs) compared with emergency medicine (EM) resident physicians in an emergency department (ED) low acuity area, and to compare patient satisfaction when cared for by MLPs versus EM residents. Methods: This was a retrospective review of EM resident physicians and MLPs in an ED low acuity area. The number of patients seen and relative value units (RVUs) generated per clinical hour worked were evaluated. A t test was used to compare resident and MLP productivity. Additionally, patients were prospectively surveyed to assess satisfaction, using survey items based on the Press-Ganey survey. Non-parametric statistics were used to analyse patient satisfaction scores. Results: MLPs treated 2.21 patients per hour (CI ±0.09), while resident physicians treated 1.53 patients per hour (CI ±0.08). MLPs generated 4.01 RVUs per hour (CI ±0.18) while resident physicians generated 3.14 RVUs per hour (CI ±0.18). Resident physicians generated 2.07 RVUs per patient (CI ±0.08) while MLPs generated 1.82 RVUs per patient (CI ±0.03; p<0.001). Of the 201 completed satisfaction surveys, 126 patients were seen by MLPs and 75 were seen by residents. Overall patients were highly satisfied with their ED visit. There were no differences in any survey responses based on provider type or resident level of training. Conclusion: In a low acuity area of the ED, MLPs treated more patients per hour and generated more RVUs per hour than EM resident physicians. However, resident physicians generated more RVUs per patient. Patient satisfaction did not differ.